2005
DOI: 10.1084/jem.20041992
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin is a hematopoietic stem cell niche component that negatively regulates stem cell pool size

Abstract: Stem cells reside in a specialized niche that regulates their abundance and fate. Components of the niche have generally been defined in terms of cells and signaling pathways. We define a role for a matrix glycoprotein, osteopontin (OPN), as a constraining factor on hematopoietic stem cells within the bone marrow microenvironment. Osteoblasts that participate in the niche produce varying amounts of OPN in response to stimulation. Using studies that combine OPN-deficient mice and exogenous OPN, we demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
478
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 607 publications
(504 citation statements)
references
References 53 publications
(61 reference statements)
21
478
1
3
Order By: Relevance
“…Nothing has been reported so for with respect to a likely connection of these cytokines and OPN in BM and aging, though a recent study reported increased IP‐10 serum levels in elderly patients (de Bonfante et al , 2015). As implied by previous studies (Nilsson et al , 2005; Stier et al , 2005; Grassinger et al , 2009), our results further confirm that OPN cleaved by thrombin is biologically active. OPN is a secreted glycoprotein able to bind HSCs through, among others, interactions with CD44 and α 9 β 1 /α 4 β 1 integrins (Stier et al , 2005; Grassinger et al , 2009).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nothing has been reported so for with respect to a likely connection of these cytokines and OPN in BM and aging, though a recent study reported increased IP‐10 serum levels in elderly patients (de Bonfante et al , 2015). As implied by previous studies (Nilsson et al , 2005; Stier et al , 2005; Grassinger et al , 2009), our results further confirm that OPN cleaved by thrombin is biologically active. OPN is a secreted glycoprotein able to bind HSCs through, among others, interactions with CD44 and α 9 β 1 /α 4 β 1 integrins (Stier et al , 2005; Grassinger et al , 2009).…”
Section: Discussionsupporting
confidence: 92%
“…As implied by previous studies (Nilsson et al , 2005; Stier et al , 2005; Grassinger et al , 2009), our results further confirm that OPN cleaved by thrombin is biologically active. OPN is a secreted glycoprotein able to bind HSCs through, among others, interactions with CD44 and α 9 β 1 /α 4 β 1 integrins (Stier et al , 2005; Grassinger et al , 2009). Thrombin‐mediated cleavage of OPN reveals a cryptic binding site in OPN for α4β1 and α9β1 integrins that are expressed on HSPCs (Smith et al , 1996; Grassinger et al , 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These niche cells express a high level of HSC maintenance factors termed "niche factors", including Angiopoietin 1 (Ang-1) (Arai et al, 2004), stem cell factor (SCF) (Heissig et al, 2002), CXCL12 (Sugiyama et al, 2006;Katayama et al, 2006;Kollet et al, 2006), thrombopoietin (Tpo) (Qian et al, 2007;Yoshihara et al, 2007), Wnt (Fleming et al, 2008), Jagged 1 (Jag1) (Calvi et al, 2003;Butler et al, 2010), TGF-β (Yamazaki et al, 2011), osteopontin (OPN) (Nilsson et al, 2005;Stier et al, 2005) CXCL4 (Bruns et al, 2014, N-cadherin (Haug et al, 2008;Hosokawa et al, 2010a;2010b), and E-selectin (Winkler et al, 2012). There are, however, still controversies in the field regarding the precise HSC niche, and a better understanding of the elements that regulate HSCs is required.…”
Section: The Hsc Niche In the Teleost Kidneymentioning
confidence: 99%
“…Retention of β-catenin at the stem cell membrane may prevent precocious activation of the Wnt signaling pathway [20]. Osteopontin (Opn), a glycoprotein that negatively regulates the pool size of HSCs in bone marrow, is also critical for breast cancer bone metastasis [70][71][72][73]. Other critical adhesion molecules required for stem cell localization include integrins [74][75][76][77][78][79].…”
Section: Stem Cell Niche and Tumor Migrationmentioning
confidence: 99%